Efficacy and safety of neoadjuvant immunotherapy protocols and cycles for non-small cell lung cancer: a systematic review and meta-analysis - Wang, Huaiyong; Liang, Song; Yu, Yue; Han, Yun (Frontiers in Oncology, 2024)
BACKGROUND: This study evaluated the use of different neoadjuvant immunotherapy cycles and regimens for non-small cell lung cancer. MATERIALS AND METHODS: Databases were searched for articles published up until December 2023. Data on the major pathologic response (MPR), complete pathologic response (pCR), radiological response, treatment-related adverse events (TRAEs), serious adverse events (SAEs), surgical resection, surgical complications, R0 resection, and conversion to thoracotomy were collected. A subgroup analysis was performed according to the treatment regimens and cycles. Stata/MP software was used for statistical analyses. RESULTS: In total, 2430 individuals were assessed from 44 studies. Compared with those following neoadjuvant immunotherapy alone (MPR/pCR/TRAEs/SAEs: ES=0.26/0.07/0.43/0.08, 95% CI: 0.18-0.34/0.04-0.10/0.28-0.58/0.04-0.14), the MPR and pCR rates, incidence of TRAEs and SAEs following neoadjuvant chemoimmunotherapy increased significantly (MPR/pCR/TRAEs/SAEs: ES=0.55/0.34/0.81/0.22, 95% CI: 0.48-0.63/0.28-0.41/0.69-0.90/0.13-0.33, P=0.001/0.002/0.009/0.034). No significant differences were found in the surgical resection, surgical complications, R0 resection, or conversion to thoracotomy. In the chemoimmunotherapy group, no statistically significant differences were found in the MPR and pCR rates, incidence of TRAEs and SAEs in the two-cycle, three-cycle and four-cycle groups (MPR/pCR/TRAEs/SAEs: ES=0.50;0.70;0.36/0.32;0.49;0.18/0.95;0.85;0.95/0.34;0.27;0.37, P=0.255/0.215/0.253/0.848). In the ICIs group, there was little change in the MPR and pCR rates, incidence of TRAEs and SAEs in the two-cycle group compared to the three-cycle group. (MPR/pCR/TRAEs/SAEs: ES=0.28;0.20/0.06;0.08/0.45;0.35/0.10;0.02, P=0.696/0.993/0.436/0.638). The neoadjuvant treatment cycle had no significant effect on surgical resection, surgical complications, R0 resection, or conversion to thoracotomy in both regimens. CONCLUSION: Neoadjuvant chemoimmunotherapy significantly increased the rate of tumor pathological remission compared to neoadjuvant immunotherapy alone but also increased the incidence of TRAEs and SAEs. The efficacy and safety of neoadjuvant chemoimmunotherapy are found to be favorable when administered for a duration of three cycles, in comparison to both two and four cycles.